Carfilzomib and dexamethasone versus eight cycles of bortezomib and dexamethasone in patients with relapsed or refractory multiple myeloma: an indirect comparison using data from the phase 3 ENDEAVOR and CASTOR trials. Issue 1 (2nd January 2020) - Weisel, Katja; Majer, Istvan; DeCosta, Lucy; Oriol, Albert; Goldschmidt, Hartmut; Ludwig, Heinz; Campioni, Marco; Szabo, Zsolt; Dimopoulos, Meletios
Abstract: In ENDEAVOR, carfilzomib and dexamethasone (Kd56) demonstrated significant improvement in progression-free survival (PFS) compared with bortezomib and dexamethasone (Vd). Both agents were administered until disease progression; the EU label for Vd, however, stipulates a maximum of eight treatment cycles. Here, matching-adjusted treatment comparison was used to compare efficacy of Kd56 with Vd, if Vd was administered for 8 cycles (Vd-8). Data from ENDEAVOR and CASTOR trials (which compared daratumumab, bortezomib, and dexamethasone with Vd-8) were used. Hazard ratios of PFS were estimated for Vd vs. Vd-8 and Kd vs. Vd-8. For cycles 1–8, risk reduction in PFS for Kd56 vs. Vd-8 was equal to that estimated in ENDEAVOR (HR: 0.53; 95% CI 0.44–0.65). Beyond eight cycles, risk reduction in PFS for Kd56 and Vd-8 was estimated to be 60% (HR: 0.40; 95% CI 0.26–0.63). The analysis suggested that PFS benefit of Kd56 over Vd increases when Vd is given for eight cycles only.